Stable Isotope Analysis of Planktonic Lower Food Webs of Lakes Erie, Huron, Michigan and Superior - John T. Lehman; Shelby Burgess (Limnological Review)
Historical plankton samples from the St. Lawrence Great Lakes were subjected to taxon-specific 15N analysis to test the hypothesis that the changes recorded in zooplankton communities during the 21st Century are related to changes in the trophic positions of large-bodied carnivorous copepods. Daphnia mendotae was used as the reference herbivore for trophic-level comparisons. The results were that Limnocalanus macrurus, Diaptomus (Leptodiaptomus) sicilis as well as the cladoceran Bythotrephes cederstroemi show evidence of elevated carnivory compared to data from the 20th Century. The large diaptomid Diaptomus (Leptodiaptomus) sicilis has a stable isotope signature that is significantly more carnivorous in Lake Superior than in Lakes Michigan and Huron by approximately one-half trophic level. Differences were found in 10 cases out of 15 for Limnocalanus (Huron, Michigan Superior), 6 cases out of 15 for Diaptomus (Huron, Michigan) and in 1 out of 1 for Senecella (Superior). We did not find evidence to support the theory that large-bodied calanoid copepods may have improved their representation in the food webs of the upper Great Lakes by shifting their trophic position downward. Instead, large-bodied Calanoida have increased their trophic positions in parallel with their increased relative abundance. More research is thus needed to explain the driving forces for changing food web dynamics in the Great Lakes.